The spontaneous symmetry breaking in Ta2NiSe5 is structural in nature - Baldini, Edoardo; Zong, Alfred; Choi, Dongsung; Lee, Changmin; Michael, Marios H; Windgaetter, Lukas; Mazin, Igor I; Latini, Simone; Azoury, Doron; Lv, Baiqing; Kogar, Anshul; Su, Yifan; et al. (Proceedings of the National Academy of Sciences - PNAS, 2023)
The excitonic insulator is an electronically driven phase of matter that emerges upon the spontaneous formation and Bose condensation of excitons. Detecting this exotic order in candidate materials is a subject of paramount importance, as the size of the excitonic gap in the band structure establishes the potential of this collective state for superfluid energy transport. However, the identification of this phase in real solids is hindered by the coexistence of a structural order parameter with the same symmetry as the excitonic order. Only a few materials are currently believed to host a dominant excitonic phase, Ta2NiSe5 being the most promising. Here, we test this scenario by using an ultrashort laser pulse to quench the broken-symmetry phase of this transition metal chalcogenide. Tracking the dynamics of the material's electronic and crystal structure after light excitation reveals spectroscopic fingerprints that are compatible only with a primary order parameter of phononic nature. We rationalize our findings through state-of-the-art calculations, confirming that the structural order accounts for most of the gap opening. Our results suggest that the spontaneous symmetry breaking in Ta2NiSe5 is mostly of structural character, hampering the possibility to realize quasi-dissipationless energy transport.